Airborne molecules released from male mouse urine affect female exploratory behavior - Redaelli, Marco; Orsetti, Alessandro; Zagotto, Giuseppe; Cavaggioni, Andrea; Mucignat-Caretta, Carla (Frontiers in Ecology and Evolution, 2014)
Male mouse urine delivers a wide range of molecules, which may be involved in intraspecific chemical communication. These include the Major Urinary Proteins (MUP), which bind volatile odorant molecules and slowly release them from urine marks. The aim of this work is to evaluate the role of volatile molecules in eliciting exploratory behavior, in comparison to MUP. Female mice were exposed to male mouse urine, either diluted or not, or to MUP stripped of ligands. Gas chromatography and mass spectrometry of the stimuli were performed to verify the presence and identify the odorant molecules in urine and to assess the absence of MUP ligands. The exploratory behavior of adult female mice was analyzed in a cage, in the presence of two stimuli on opposite sides, but preventing direct contact with them. Four stimuli were presented in pairs: adult male mouse urine, MUP stripped of ligands, urine diluted 100 times and water as control. The results show that adult female mice explore urine, as little as 150 nl, but do not explore MUP stripped of ligands. These data show that male urine airborne molecules, effective at very low doses, mediate initial stimulus exploration by female mice.